"Here it is safe to assume nothing at all": aesthetics and the impasse of South African poetry criticism. (3rd May 2016) - Sole, Kelwyn
ABSTRACT: This intervention highlights the question of literary evaluation and aesthetics in contemporary South African poetry in English. It suggests that the antinomy of 'formal' versus 'sociological' approaches, first criticised by Cronin three decades ago, is still present, and mars any attempt by critics to understand, appreciate and assess the diversity of the output of South African poets more fully. This flaw has become more noticeable and more vexed in the contemporary situation of global flows of information and influence, inter alia via the internet. This is exemplified in a brief analysis of two contemporary South African poets, Khulile Nxumalo and Lesego Rampolokeng. Using the formulations in Jahan Ramazani's recent A transnational poetics as a starting point, the article suggests ways in which the present critical impasse might be addressed.